ANALISIS PERBANDINGAN PENDAPATAN USAHA KOPRA PUTIH DENGAN MENGGUNAKAN PENGOLAHAN OVEN DAN SOLAR DRYER DOME DI UMKM JR AGRO INDONESIA - Lawani, Pamela; Pangemanan, Sifrid S.; Kalalo, Meily Y. B. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
White copra is dried fruit flesh through a drying process using a dryer so that the quality of the copra is better, the water content is small and clean. White copra is processed using two processes, namely oven processing and solar dryer dome. This study aims to analyze the comparison of white copra business income by using oven processing and solar dryer dome at JR Agro Indonesia. The data analysis method used is high and low Points, income analysis and R/C ratio. The results showed that the total production cost of processing the oven was Rp. 184,561,202 while the total production cost of processing the solar dryer dome was Rp. 189.991,500. Total revenue from oven processing is Rp. 240,000,000 then total revenue from solar dryer dome processing is Rp. 240,000,000 and income received using oven processing is Rp. 55,438,798 while income received using solar dryer dome processing is Rp. 50,008,500. it can be concluded that there is a comparison of the income received between the processing of the oven and the solar dryer dome. The results of the analysis of the cost efficiency of processing white copra using oven processing are 1.30 while the processing of solar dryer dome is 1.26. This means that white copra business using oven processing and solar dryer dome is cost efficient and feasible to run because the results are more than 1.